Reconstruction of patient-specific cerebral aneurysm model through image segmentation - Hong, Lim Seh; Mohd Azrul Hisham, Mohd Adib; Mohd Shafie, Abdullah; Nur Hartini, Mohd Taib; Radhiana, Hassan; Azian, Abd Aziz (Springer, Singapore, 2021)
The diagnostic assessment of cerebrovascular disease makes use of computational simulation as a predicting tool to determine hemodynamics factor contributing to the disease from patient-specific models which imitate the actual shape of the object of interest. However, the patient-specific models are generally reconstructed from the medical images subjectively. Image segmentation is commonly performed to produce object of interest with high visualization. In order to produce patient-specific anatomical model, a systematic adjustment on image intensity was performed in this study. This paper tends to present the reconstruction of three-dimensional (3D) patient-specific cerebral aneurysm model through systematic image segmentation by using threshold coefficients,